2018
DOI: 10.1084/jem.20181639
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting antibiotic-resistant Enterobacteriaceae by microbiota-mediated intracellular acidification

Abstract: Klebsiella pneumoniae, Escherichia coli, and other members of the Enterobacteriaceae family are common human pathogens that have acquired broad antibiotic resistance, rendering infection by some strains virtually untreatable. Enterobacteriaceae are intestinal residents, but generally represent <1% of the adult colonic microbiota. Antibiotic-mediated destruction of the microbiota enables Enterobacteriaceae to expand to high densities in the colon, markedly increasing the risk of bloodstream invasion, sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(176 citation statements)
references
References 46 publications
9
153
0
Order By: Relevance
“…Measuring the OD of C. rodentium over time, we noticed significantly impaired growth at higher concentrations of butyrate at a pH value of 6.0, whereas acetate and propionate did only partially reduce the growth of C. rodentium at pH 6.0 at high physiological concentrations. No significant effect for any SCFA was visible at neutral pH in line with findings on other Enterobacteriaceae [26] (Fig 6B). These results indicated that higher concentrations of SCFAs, especially butyrate, as seen in the SPF-R mice are able to abrogate growth of C. rodentium in vitro.…”
Section: Plos Pathogenssupporting
confidence: 87%
See 2 more Smart Citations
“…Measuring the OD of C. rodentium over time, we noticed significantly impaired growth at higher concentrations of butyrate at a pH value of 6.0, whereas acetate and propionate did only partially reduce the growth of C. rodentium at pH 6.0 at high physiological concentrations. No significant effect for any SCFA was visible at neutral pH in line with findings on other Enterobacteriaceae [26] (Fig 6B). These results indicated that higher concentrations of SCFAs, especially butyrate, as seen in the SPF-R mice are able to abrogate growth of C. rodentium in vitro.…”
Section: Plos Pathogenssupporting
confidence: 87%
“…It is widely acknowledged that the intestinal microbiota has enormous impact on the individual susceptibility against invading pathogens and the severity of intestinal inflammation via direct and immune-mediated mechanisms [1]. Especially reduction of the colonization resistance against certain Enterobacteriaceae such as Salmonella [5], E. coli or K. pneumoniae [26] after antibiotic treatment has been linked with a reduction of SCFA-producing bacteria. In the present study, we focus on the impact of naturally occurring variations in the microbiota composition of laboratory mice and the influence of specific members in the microbiota in murine C. rodentium infection without any antibiotic interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCFAs production by microbiota has been associated with pathogen inhibition to benefit the host (50). Physiological levels of SCFAs are reported to reduce Enterobacteriaceae members by pH mediated action (51). Specifically, propionate production by a propionate producing consortium has been shown to reduce antibiotic induced dysbiosis (52).…”
Section: Resultsmentioning
confidence: 99%
“…81 Indeed, the functional metabolic capabilities of certain commensals confer protection against pathogen infection, which is attributable to the intracellular acidification of pathogens mediated by SCFAs. 82 High concentrations of SCFAs and the acidic environment reverse or counteract the competitive advantage that O 2 and NO 3 respiration provide to facultative anaerobes such as Enterobacteriaceae. 82 Conversely, antibiotic treatment elicits gut dysbiosis and SCFA exhaustion, which further inhibits the PPAR-γ signaling pathway and induces metabolic reprogramming.…”
Section: Scfas Confer Colonization Resistance Against Intestinal Pathmentioning
confidence: 99%